2020
DOI: 10.1111/apha.13604
|View full text |Cite
|
Sign up to set email alerts
|

ZFHX3 knockdown dysregulates mitochondrial adaptations to tachypacing in atrial myocytes through enhanced oxidative stress and calcium overload

Abstract: Aim To investigate the role of zinc finger homeobox 3 gene (ZFHX3) in tachypacing‐induced mitochondrial dysfunction and explore its molecular mechanisms and potential as a therapeutic target in atrial fibrillation (AF). Methods Through a bioluminescent assay, a patch clamp, confocal fluorescence and fluorescence microscopy, microplate enzyme activity assays and Western blotting, we studied ATP and ADP production, mitochondrial electron transfer chain complex activities, ATP‐sensitive potassium channels (IKATP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…To the best of our knowledge, there are no previous data demonstrating a regulatory role of Zfhx3 on Nav1.5 channels. Conversely, data showing its effects on the expression and function of cardiac K + channels are more abundant [ 4 , 27 , 28 ]. It was shown that Zfhx3 silencing in HL-1 cells increased the expressions of Kv1.4, Kv1.5 and Kir3.4 channels, which resulted in augmented ultra-rapid delayed rectifier (I Kur ), transient outward (I to ) and acetylcholine-sensitive potassium (I KAch ) currents and the shortening of the action potential duration [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there are no previous data demonstrating a regulatory role of Zfhx3 on Nav1.5 channels. Conversely, data showing its effects on the expression and function of cardiac K + channels are more abundant [ 4 , 27 , 28 ]. It was shown that Zfhx3 silencing in HL-1 cells increased the expressions of Kv1.4, Kv1.5 and Kir3.4 channels, which resulted in augmented ultra-rapid delayed rectifier (I Kur ), transient outward (I to ) and acetylcholine-sensitive potassium (I KAch ) currents and the shortening of the action potential duration [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that Zfhx3 silencing in HL-1 cells increased the expressions of Kv1.4, Kv1.5 and Kir3.4 channels, which resulted in augmented ultra-rapid delayed rectifier (I Kur ), transient outward (I to ) and acetylcholine-sensitive potassium (I KAch ) currents and the shortening of the action potential duration [ 27 ]. More recently, Lkhagva et al described that Zfhx3 silencing in HL-1 cells led to a significant increase in the ATP-sensitive K current (I KATP ) [ 28 ]. There are also data suggesting that Zfhx3 regulates intracellular calcium handling, since Zfhx3 knockdown in HL-1 cells increased the ryanodine receptor ( RYR2 ), RyR2 p2808, and SERCA2a ( ATP2A2 ) mRNA expression [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Today, bioluminescence-based experimental techniques using enzymatically active luciferin are widely available, aiding molecular physiology in fields as diverse as cardiovascular research, pancreatic ß cell synchronization or general cellular physiology. [4][5][6] From the simplest patches of photoreceptor protein in unicellular animals to complex compound eyes, manifold organisms develop various photoreceptors. This occurs in simple to highly complex species, in close adaptation to the environment and its demands.…”
Section: Illuminating Physiologymentioning
confidence: 99%
“…Animals emit light to lure prey or potential mates, or to hide by camouflage and mimicry. Today, bioluminescence‐based experimental techniques using enzymatically active luciferin are widely available, aiding molecular physiology in fields as diverse as cardiovascular research, pancreatic ß cell synchronization or general cellular physiology 4–6 …”
mentioning
confidence: 99%
“…ZFHX3 and FZD9 are two other genes associated with significant CpGs that have potentially important functions, including ZFHX3's involvement in regulating both intracellular calcium homeostasis (Zhao et al, 2019) and mitochondrial oxidative stress (Lkhagva et al, 2021), and FZD9's involvement in bone mineralization (Albers et al, 2011;Heilmann et al, 2013) andB-cell development (Ranheim et al, 2005). Bone mineralization is a pathway that also arose in our GWAS biomarker research (ACVR1, BMPRB) (Taylor et al, 2020) and has implications for calcium regulation.…”
Section: Bioinformaticsmentioning
confidence: 99%